From Orientalsim to Postcoloniality (American Journal of Islam and Society, 2006)
Orientalsim and postcoloniality are synonymous with contemporary cultureand literature. As much as the younger generations of formally colonizednations and communities would like to argue, the truth of the matter is that on some level, their colonial times have made an everlasting impression ontheir own identity and culture. This was one of the many themes that theconference, held at the Södertörns Högskola University College in Stockholm,Sweden, focused on during its congested four-day program.This was one of the largest gatherings to deal with issues of ethnic identityand diversity, as well as the non-proverbial influences of colonialism inthe reshaping of new communities and their modernized cultures. Paperspresented ranged from diversity and nationalism in the postcolonial context,postcolonialsim and religious studies, African-American writing and socialactivism, colonial romanticism and white supremacy, and postcolonial literatureand film in English, among other topics ...